Associations of Platelet Count with Inflammation and Response to Anti-TNF-α Therapy in Patients with Ankylosing Spondylitis - Qian, Hongyan; Chen, Rongjuan; Wang, Bin; Yuan, Xiaoqing; Chen, Shiju; Liu, Yuan; Shi, Guixiu (Frontiers in Pharmacology, 2020)
Background: Increased platelet count has been reported in ankylosing spondylitis (AS) patients, but its clinical significance is still largely elusive. The objective of this study was to evaluate the clinical role of platelet count in AS patients especially its impact on treatment outcomes. Methods: A case-control study containing 35 AS patients receiving anti-tumor necrosis factor-α (anti-TNF-α) therapy and 45 healthy controls was performed, and AS patients were followed at least 6 months after anti-TNF-α therapy. A systematic review and meta-analysis of studies containing relevant data on outcomes of interest was also performed. Results: AS patients had significantly higher platelet count than controls (P=0.0001), and the significantly increased platelet count in AS patients was confirmed in a meta-analysis of 14 studies involving 1,223 AS patients and 913 controls (Mean difference = 39.61, 95%CI 27.89-51.34, P<0.001). Besides, platelet count was significantly correlated with ESR (P<0.001) and was moderately correlated with ASDAS-CRP score (P=0.002). Moreover, anti-TNF-α therapy could reduce platelet count in AS patients at the first month and the effect was maintained through the treatment duration. In the prospective follow-up study of those 35 AS patients, those responders to anti-TNF-α therapy had significantly lower platelet count than non-responders (P=0.015). Logistic regression analysis suggested that lower platelet count was associated with higher possibility of achieving good response to anti-TNF-α therapy in AS patients (Odds ratio = 2.26, 95%CI 1.06-4.82; P=0.035). Conclusion: This study suggested that platelet count was associated with inflammation severity and treatment outcomes in AS patients, and elevated platelet count was a promising biomarker of poorer response to anti-TNF-α therapy. The findings above need to be validated in more future studies.